Sensitivity of gross margin for field crops - Anca Dachin; Ana Ursu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 7th Edition of the International Symposium, November 2016, Bucharest, 2016)
A major issue of agriculture in Romania is to achieve the level of profitability of farms which ensures their economic viability. In this respect farms seek profitability of each product. The gross margin is a measure of profitability, which for the field crops is determined by the producer price, yield per hectare and variable costs. Since some of the crops are not profitable every year, subsidies also play an important role in economic calculation. The paper aims to estimate the sensitivity of the gross margin to changes of these factors in the case of cereals, sunflower, soybean, potato and beet. The sensitivity analysis relies on estimated data regarding the crop in 2015/2016 and has the purpose to explore the impact of assumptions of changes in determinants on the results measured by gross margin. The sensitivity of gross margin is the highest and also similar in relation to the producer price and the yield per hectare.
Keywords: Q02; C63; H25; 330; gross margin; sensitivity; field crops